2006
DOI: 10.1159/000094456
|View full text |Cite
|
Sign up to set email alerts
|

Acute Gastric Volvulus: Diagnosis and Management over 10 Years

Abstract: Background/Aims: Gastric volvulus is a rare, potentially life-threatening condition, which is difficult to diagnose. This study represents a series of patients with acute gastric volvulus. Methods: All patients presenting with acute gastric volvulus over a 10-year period were reviewed. Results: Twenty-one patients with a median age of 66 years were identified. Acute gastric volvulus was secondary to a paraesophageal hiatus hernia in 16 patients. The major symptoms were abdominal pain, vomiting and upper gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
60
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 21 publications
2
60
0
3
Order By: Relevance
“…A combination of both is the rarest form [5,6]. Gastric volvulus can present either as an acute or chronic presentation, classical triad is present in 70% of the cases presenting as severe epigastric abdominal pain and distension, vomiting followed by non-productive retching, and inability to pass NG tube [1-3]. In a review looking at 21 patients, it was found that abdominal pain, vomiting and upper GI bleeding were the most common presenting symptoms [1].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A combination of both is the rarest form [5,6]. Gastric volvulus can present either as an acute or chronic presentation, classical triad is present in 70% of the cases presenting as severe epigastric abdominal pain and distension, vomiting followed by non-productive retching, and inability to pass NG tube [1-3]. In a review looking at 21 patients, it was found that abdominal pain, vomiting and upper GI bleeding were the most common presenting symptoms [1].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric volvulus can present either as an acute or chronic presentation, classical triad is present in 70% of the cases presenting as severe epigastric abdominal pain and distension, vomiting followed by non-productive retching, and inability to pass NG tube [1-3]. In a review looking at 21 patients, it was found that abdominal pain, vomiting and upper GI bleeding were the most common presenting symptoms [1]. The chronic presentation on the other hand could manifest with recurrent non-specific abdominal pain, abdominal fullness, chest pain, retching, acid reflux, and dysphagia [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations